Gambaran Tingkat Pengetahuan Ibu tentang Feeding Rules pada Batita Gerakan Tutup Mulut (GTM) - Nur Chumairoh; Indah Ika Suryaningsih H (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2021)
Introduction: Feeding is an important part of the life of infants and children under three years (toddler) and most parent-child interactions occur at feeding time. However, 50 of parents reported that their children have feeding problems. About 1-2% of babies experience a serious Mouth Shut Movement (MSM) that can lead to malnutrition. Feeding rules can help toddlers to manage and to overcome their own eating problems. Purpose: This study aims to determine the knowledge about Feeding rules of mothers who have children aged 1-3 years with Mouth Shut Movement (MSM) in the area of the General Hospital of the Muhammadiyah University of Malang. Methods: This study is a descriptive study and uses an observational design. The participants were selected through purposive sampling among mothers who have children with Mouth Shut Movement (MSM) aged 1-3 years with total of 67 respondents. Respondents were asked to fill out a questionnaire in the form of a google form. Validity and reliability tests have been carried out with a Cronbach Alpha value of 0.899 and univariate analysis was used for the data analysis. Results: The result shows that 38 respondents (57%) have good knowledge about feeding rules while 29 respondents (43%) have lacked it. Discussion: It indicates that even though the mother's level of knowledge about feeding rules is good, it did not guarantee that the children did not experience Mouth Shut Movement (MSM). This could be due to other internal factors in the child's own body. Conclusion: The conclusion is knowledge about feeding rules of mothers who have children aged 1-3 years with Mouth Shut Movement (MSM) is good.